Capturing Irradiation with Nanoantennae: Plasmon‐Induced Enhancement of Photoelectrolysis. Issue 12 (3rd May 2017) - Daccache, Layal; Zeller, Sven; Jacob, Timo
Abstract: In solving the energy challenge of solar irradiation′s inconsistency, a desirable approach is mimicking nature′s photosynthesis by collecting and storing solar energy via water splitting. TiO2 is a promising candidate, a wide‐gap semiconductor with low cost, high efficiencies in the UV region, and photostability. Its shortcomings in the visible spectrum can be improved via band gap engineering, mainly co‐catalyst doping, thereof Au nanoparticles. In contrast, we deposit a structured semiconductor on a plasmonic‐active co‐catalyst: we reverse the species order with respect to illumination and achieve a patterned structure for both species in which TiO2 pillars are grown on a Raman‐active Au substrate. The pillars act as antennae, coupling incoming light absorption while feeding on the substrate′s plasmonic effects. The aforementioned system shows impressive incident‐photon‐to‐current efficiencies (IPCEs) in the visible region, along with increased photocurrents in the UV and red shifts depending on deposition depth, diameter, and annealing temperature. We were able to tune the system′s photoresponse by changing the nanostructure geometry and therewith tuned the resonance to the incoming irradiation. Abstract : Upside‐down catalyst : In contrast to the widely used photoelectrocatalysts consisting of Au nanoparticles on a TiO2 substrate, the authors reverse the species order and achieve a patterned structure in which TiO2 pillars are grown on a Raman‐active Au substrate. This system shows excellent incident‐photon‐to‐current efficiencies in the visible region along with increased photocurrents in the UV.